(untitled) (Research, Society and Development, 2020)
Objective: To describe the perception of occupational therapists about their practices in the services of the 24h Psychosocial Care Center. Methodology: This is a descriptive study of a qualitative nature, carried out with six occupational therapists linked to two 24h Psychosocial Care Centers in a municipality in the Northeast of Brazil. Participants were interviewed using a semi-structured questionnaire, the responses were transcribed in full and subsequently analyzed using the content analysis technique. Results: From the professional reports, nine discursive categories emerged, which deal with the perceptions of occupational therapists in relation to: the profile of the professionals; their perception of the functioning of the 24h Psychosocial Care Centers, highlighting the difficulties and challenges faced in daily clinical practice; suggestions for improvements; the therapeutic strategies carried out and how they impact the service users’ lives. Conclusion: Based on the professionals’ discernments, it was possible to highlight the importance of interdisciplinarity in health actions in the multidisciplinary service team, which faces obstacles in terms of network articulation, matrix support and reception. The potential of occupational therapy in CAPS services was observed through the therapeutic modalities offered, among them group activities were highlighted by the interviewees as facilitators in the process of intervention and psychosocial rehabilitation of users.